Perancangan Buku Prosa Visual “Seduhan Terakhir di Ambang Rimba” Sebagai Implementasi Transmedia Storytelling dalam Literasi Lingkungan Tesso Nilo - Puspa Aulia Putri; Arkhadies Hanif Medina; Iwan Koswara; Rinda Aunillah Sirait (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
The implementation of transmedia storytelling in the visual prose book "Seduhan Terakhir di Ambang Rimba" represents an effort to construct a profound and emotional medium for environmental literacy. Designed as a narrative extension of the two-dimensional animation of the same title, this book aims to enrich the audience's experience regarding deforestation in Tesso Nilo National Park, Indonesia. The narrative highlights the inner monologue of Nilo, a Sumatran elephant acting as both a witness and a victim of forest destruction, utilizing a reflective and introspective approach. The book employs digital illustrations with a watercolor style and a dominant earth-tone palette to establish a melancholic atmosphere, depicting the isolation and loss experienced by the protagonist. Through a transmedia storytelling approach, this book does not merely retell the story presented in the animation but offers a new, deeply emotional narrative layer, providing space for the audience to contemplate the environmental issues raised. Ultimately, this book aims to deliver a more personal experience, evoking the audience's empathy toward the ecological impact of environmental degradation and strengthening their awareness of the importance of nature conservation.